Representasi Bapak dalam Film Pendek Berjudul “BAPAK” (Analisis Semiotika John Fiske) - Althaf, Muhammad Alfito (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2025)
In patriarchal culture, fathers are often considered as the head of the family who is responsible for the economic welfare and the main decision maker in the household. As time goes by, perceptions of the figure of the father also vary greatly due to the influence of the culture in which he is located. This study aims to represent the figure of the father in Javanese culture through a short film entitled "BAPAK". The researcher uses a descriptive qualitative research approach to understand the phenomenon of the object being studied as a whole. The research data collection technique will be carried out by direct observation through the short film "Bapak". The researcher uses John Fiske's semiotic analysis to analyze moving images such as films and TV shows through 3 levels of television code theory. The results of this study indicate that the film effectively represents a father who has his own way of showing affection and responsibility towards his family, such as being a hard worker, giving affection and attention, and being willing to sacrifice for the happiness of his family. The conclusion that can be drawn is that the film Bapak is not only an emotionally touching work of art, but also conveys a strong social message about the importance of a father's role in family life.